PTU-134 An audit of ercp in a dgh hospital in which ptc is not practiced. (22nd June 2015) - Manda, V; Blackhall, V; Gibson, S; Sharp, C; Robertson, K
Abstract : Introduction: The audit was undertaken to provide accurate success and complication rates to patients undergoing ERCP. Although PTC is available within the Health Board it is not practiced in the endoscopist's base hospital. Laparoscopic bile duct exploration is normally reserved for cases of failed endoscopic stone clearance. Method: Consecutive procedures from a single endoscopist's practice were included. Data on indications, results and early complications were collected prospectively. Results: 162 procedures from an 8 months period were studied. In 119 (73%) the ampulla was intact (no earlier sphincterotomy). The majority of cases, 112 (69%), were undertaken for gallstone disease, 36 (22%) for cancers and 9 (6%) for post surgical biliary leaks. One each was performed for sphincterotomy stenosis, stent within the CBD and blood clot. In 2 cases cholangiography showed no pathology but in each there had been concern of choledocholithiasis and MRI was contraindicated by cardiac pacemaker. In 10 cases biliary cannulation failed; 6.2% of all cases and 8.4% of intact ampullae. Only four were repeated, each with success. Of the remaining 6, 3 had massive duodenal distortion from cancers and required PTC. For one the treating surgeon elected surgery in the form of cholecystectomy and choledocho-duodenostomy. One was during stent removal after treatment of cystic duct stump leak and was not pursued when the patient became restless. The last died of unrelated causes awaiting repeat procedure. There were no deaths during the immediate post-operative period. Complications occurred in 19 (12%) of procedures. The commonest complication was acute pancreatitis. It occurred in 13 (8.0%) cases of which 12 were mild and quickly self-limiting. In the other, respiratory failure responded to conservative measures. No surgical or radiological intervention was required. In 3 (1.9%) cases bleeding occurred requiring laparotomy, endostasis and transfusion in one case each. Two (1.2%) cases had post-operative sepsis requiring intravenous antibiotics. There was one iatrogenic perforation of a hiatus hernia that was successfully managed conservatively. Complications occurred in 7.0% (3 complications) of procedures with earlier sphincterotomy compared to 13.4% (16 complications) of procedures where the ampulla was intact. Bleeding, perforation and severe pancreatitis only complicated those cases where the ampulla was intact. Conclusion: ERCP can be practiced successfully in a DGH setting but complication rates are not insignificant. Complications are twice as common in those having an intact ampulla and may be more severe in this group. Disclosure of interest: None Declared.